TURKISH-GREEK RELATIONS AND THE CYPRUS QUESTION: QUO VADIS? - Aksu, Fuat (UNIV COMPLUTENSE MADRID, SERVICIO PUBLICACIONES, 2010)
It can be claimed that the most disruptive factor in the intransigent relations between Turkey and Greece is the absence of a platform for dialogue and negotiation where constructive relations might be developed. The efforts made towards dialogue and negotiation, initiated from time to time, were inadequate given the absence of trust and security between the two countries. The process of moderate dialogue and confidence building measures initiated after the crisis of the 1990s created the basis for the bilateral detente in 1999. During this period, once the EU conferred candidate status on Turkey, the questions between Turkey and Greece were moved from the traditional sphere to the European platform. In other words, relations and disputes were Europeanized. In the post-1999 period, bilateral relations were developed under the axis of conditionality and Europeanization. Even though this situation created an appropriate basis for the development of dialogue and cooperation, it was not able to mark an improvement in solving the fundamental questions. In particular, the acceptance of the Greek Cypriots into the European Union despite their rejection of the Annan Plan altered the balance against Turkish Cypriots and Turkey, and thus Turkish criticism of the European Union increased. The detente process reinforced the opinion that it was possible to live with the over-securitized problems of the past and increase the level of tolerance in bilateral realtions. However, tense relations which the European anchor can prevent at present might take shape in the foreseeable future, if the European Union cannot provide full membership to Turkey.
Keywords: Turkish - Greek relations; Cyprus; Detente; Europeanization; International Relations